1992
DOI: 10.1088/0953-8984/4/32/005
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in silver bromide at the melting point

Abstract: AbslraeL A neutron diffraction study has kea performed on AgBr at a series d temperalum from 293K U) 706K (melting point, T , = 701 K). including measuxmenls as close as 0.3f0.05' from T .. Analysis of the smciure lacion using the reverse Monte Carlo modelling technique indicates that the motion of the Ag+ ions about lheir mcksall lattice sites is anisolmpic, wilh incxasing Occupancy o f the (fit) tetrahedral interstitial site as the melting point is approached. It ir mncluded that the silver sub-lattice is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
55
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 15 publications
10
55
0
Order By: Relevance
“…In [12] we suggested that the effect should be explained in terms of the frequent hopping of silver ions from their regular octahedral lattices sites into tetrahedral inter stitial sites and back again, i.e., by the frequent cre ation and recombination of Frenkel pairs. This inter pretation would be in agreement with structural data showing significant silver-ion probability density be tween lattice sites and interstitial sites [15][16][17].Our present measurements include angular fre quencies that are of the order of, and even larger than, the inverse time constant of the Debye-type process. In fact, the numerical value of this time constant has been unknown up to now.…”
supporting
confidence: 91%
“…In [12] we suggested that the effect should be explained in terms of the frequent hopping of silver ions from their regular octahedral lattices sites into tetrahedral inter stitial sites and back again, i.e., by the frequent cre ation and recombination of Frenkel pairs. This inter pretation would be in agreement with structural data showing significant silver-ion probability density be tween lattice sites and interstitial sites [15][16][17].Our present measurements include angular fre quencies that are of the order of, and even larger than, the inverse time constant of the Debye-type process. In fact, the numerical value of this time constant has been unknown up to now.…”
supporting
confidence: 91%
“…This could be attributed to the difference detected in the position of the minimum for the pair potential. It is also stressed here that the present result of the inter-atomic distance for the nearest neighbor Ag±Br pair agrees well with the values determined by neutron diffraction [12,13].…”
Section: Molten Agbrsupporting
confidence: 90%
“…15.48 As for AgCl and AgBr, the ionic conductivity is due to the cationic Frenkel defects, and it is suggested that a possible diffuse transition to a superionic state is frustrated by the disordering of the anionic sublattice due to Schottky defects which leads to melting. 49,50 This behavior may be because the size difference between cations and anions in CuCl is less pronounced than in AgI and CuI, and also because the chloride polarizability s lower than the iodide one. To answer this question would be necessary to carry out MD simulations of CuCl before melting using non-cubic boundary conditions, which are not available in our own programs, as it is the case in many standard MD simulation software.…”
Section: Discussionmentioning
confidence: 99%